2013
DOI: 10.1016/j.encep.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Le portrait des mères néonaticides dans les expertises judiciaires

Abstract: Recherche financée par l'Observatoire National de l'Enfance en Danger, la région Ile-de-France, la Fondation pour la recherche en Psychiatrie et en santé mentale, la Fondation Wyeth pour la santé de l'enfant et de l'adolescent.Remerciements à Pascale Gerbouin-Rérolle responsable du recueil des données. 3The profile of neonaticide mothers in legal expertise Key words: infanticide, maternal behaviour, personality, intergenerational relations, forensic psychiatry. IntroductionNeonaticide is the term used to refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Early research demonstrated that neonaticide perpetrators differ from other filicide perpetrators regarding motives and individual traits (Resnick 1970 ). However, the group of women who commit neonaticide show common characteristics (Amon et al 2012 ; Putkonen et al 2007 ; Vellut et al 2013 ). As filicide, and particularly neonaticide, are inconceivable crimes and difficult for the public to understand, cases involving mothers killing more than one newborn over time are even harder to comprehend.…”
Section: Introductionmentioning
confidence: 99%
“…Early research demonstrated that neonaticide perpetrators differ from other filicide perpetrators regarding motives and individual traits (Resnick 1970 ). However, the group of women who commit neonaticide show common characteristics (Amon et al 2012 ; Putkonen et al 2007 ; Vellut et al 2013 ). As filicide, and particularly neonaticide, are inconceivable crimes and difficult for the public to understand, cases involving mothers killing more than one newborn over time are even harder to comprehend.…”
Section: Introductionmentioning
confidence: 99%
“…Si l'abolition du discernement, qui peut inciter la justice à conclure à une irresponsabilité pénale est très rare dans les affaires de néonaticide, la reconnaissance de l'altération du discernement est par contre fréquente, selon une étude réalisée à partir d'expertises judiciaires. Cette reconnaissance protège, comme le législateur le prévoyait, des peines les plus lourdes (Vellut and Simmat-Durand, 2013). Cette notion peut être systématiquement employée dans d'autres pays où le législateur considère que les circonstances d'un accouchement imprévu et solitaire sont de nature à altérer le discernement (Putkonen et al, 2007a).…”
Section: Les éLéments Liés à La Procédureunclassified